Fructan synthesis, accumulation, and polymer traits. I. Festulolium chromosome substitution lines - Gallagher, Joe A.; Cairns, Andrew J.; Thomas, David; Charlton, Adam; Williams, Peter; Turner, Lesley B. (Frontiers in Plant Science, 2015)
The fructans found as storage carbohydrates in temperate forage grasses have a physiological role in regrowth and stress tolerance. They are also important for the nutritional value of fresh and preserved livestock feeds, and are potentially useful as feedstocks for biorefining. Seasonal variation in fructan content and the capacity for de novo fructan synthesis have been examined in a Festulolium monosomic substitution line family to investigate variation in the polymers produced by grasses in the ryegrass-fescue complex. There were significant differences between ryegrass and fescue. Fescue had low polymeric fructan content and a high oligomer/polymer ratio; synthesis of polymers longer than degree of polymerisation 6 (DP6) from oligomers was slow. However, extension of polymer length from DP10/DP20 upwards appeared to occur relatively freely, and, unlike ryegrass, fescue had a relatively even spread of polymer chain lengths above DP20. This included the presence of some very large polymers. Additionally fescue retained high concentrations of fructan, both polymeric and oligomeric, during conditions of low source/high sink demand. There were indications that major genes involved in the control of some of these traits might be located on fescue chromosome 3 opening the possibility to develop grasses optimised for specific applications.